Application of Measure of Noncompactness to Volterra Equations of Convolution Type - Lizama-Yanez, C (Rocky Mountain Mathematics Consortium, 2016)
Sufficient conditions for the existence of at least one solution of a nonlinear integral equation with a general kernel are established. The existence result is proved in C([0, T], E), where E denotes an arbitrary Banach space. We use the Darbo-Sadovskii fixed point theorem and techniques of measure of noncompactness. We extend and generalize results obtained by other authors in the context of fractional differential equations. One example illustrates the theoretical results.